Rafferty's Last Case : A Minnesota Mystery featuring Sherlock Holmes - Millett, Larry, 1947- (Book collections on Project MUSE., 2022)
"When news of Shadwell Rafferty's death reaches Sherlock Holmes, the world's most famous detective and his redoubtable companion Watson rush to Minnesota to hunt for their friend's killer. Set amid the glittering society and sordid underworld of 1928 St. Paul, Larry Millett's ninth and final Shadwell Rafferty mystery takes readers through the serpentine twists of Rafferty's fatal investigation"--